2016
DOI: 10.1103/physrevd.94.123503
|View full text |Cite
|
Sign up to set email alerts
|

Moduli backreaction on inflationary attractors

Abstract: We investigate the interplay between moduli dynamics and inflation, focusing on the KKLTscenario and cosmological α-attractors. General couplings between these sectors can induce a significant backreaction and potentially destroy the inflationary regime; however, we demonstrate that this generically does not happen for α-attractors. Depending on the details of the superpotential, the volume modulus can either be stable during the entire inflationary trajectory, or become tachyonic at some point and act as a wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…For scalar EFTs Lie-algebraic approaches have been presented in [23,24] while in [25] these methods were used to prove that a gauge vector cannot be a Goldstone mode of a spontaneously broken space-time symmetry without introducing new degrees of freedom. This implies that the Born-Infeld (BI) vector is not special from the perspective of non-linear symmetries and enhanced soft limits (the same result was found in [8] where it was shown that the BI vector has a vanishing soft weight).Recently, we presented an algorithm for an exhaustive classification of the possible algebras which can be non-linearly realised on a set of Goldstone modes with linearly realised Poincaré symmetries 4 and canonical propagators in [26]. We illustrated this with EFTs of multiple scalars and multiple spin-1/2 fermions.…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…For scalar EFTs Lie-algebraic approaches have been presented in [23,24] while in [25] these methods were used to prove that a gauge vector cannot be a Goldstone mode of a spontaneously broken space-time symmetry without introducing new degrees of freedom. This implies that the Born-Infeld (BI) vector is not special from the perspective of non-linear symmetries and enhanced soft limits (the same result was found in [8] where it was shown that the BI vector has a vanishing soft weight).Recently, we presented an algorithm for an exhaustive classification of the possible algebras which can be non-linearly realised on a set of Goldstone modes with linearly realised Poincaré symmetries 4 and canonical propagators in [26]. We illustrated this with EFTs of multiple scalars and multiple spin-1/2 fermions.…”
mentioning
confidence: 53%
“…A second possibility is the Special Galileon [32,36] which has been studied from various directions [37,38]. In our recent paper [26] we have demonstrated from an algebraic perspective that these are the only two exceptional algebras and EFTs for a single scalar field. Moreover, in the context of fermionic Goldstones, we proved that the only exceptional EFT is that corresponding to Volkov-Akulov (VA) [39] and its multi-field extensions which nonlinearly realise supersymmetry (SUSY) algebras 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The distance between the electrodes h = 3.8 cm. The system characteristic relaxation time is therefore θ = h 2 /(π 2 D) = 29 hrs, cf.…”
Section: Resultsmentioning
confidence: 99%